2022
DOI: 10.1017/s1368980022000799
|View full text |Cite
|
Sign up to set email alerts
|

Impact of school meals on educational outcomes in Addis Ababa, Ethiopia

Abstract: Objective: This study evaluated the impact of the Addis Ababa SFP on educational outcomes. Design: Single-group repeated measurement/longitudinal study design and multistage stratified sampling design was followed. Effect sizes estimates, repeated measures ANOVA, Chi-square, Generalized Additive Mixed Model, and mixed effects negative binomial regression were used. Academic scores, attendance and dropout, and height and weight of schoolchildren were collected. Setting: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
5
0
3
Order By: Relevance
“…The studies showed mixed results. Some of the findings conclude that the implementation of a school feeding program enhances academic achievement, [ 35 , 40 – 42 ] raises class attendance, [ 30 , 31 , 40 , 43 – 50 ] reduces dropout rates, [ 42 – 44 , 49 ] and increases enrollment. [ 40 , 42 , 48 , 50 ] On the other hand, a study reported that stopping SFP increases male enrollment, and decreases class repetition [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The studies showed mixed results. Some of the findings conclude that the implementation of a school feeding program enhances academic achievement, [ 35 , 40 – 42 ] raises class attendance, [ 30 , 31 , 40 , 43 – 50 ] reduces dropout rates, [ 42 – 44 , 49 ] and increases enrollment. [ 40 , 42 , 48 , 50 ] On the other hand, a study reported that stopping SFP increases male enrollment, and decreases class repetition [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…School feeding programs showed improved nutritional status among school children in Addis Ababa. 43 The study has insights into both the epidemiology of S. mansoni and the clinical features experienced by the school children. This will help to understand the burden of the disease and enhance strengthening interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Los hallazgos encontrados en las investigaciones empíricas dejan ver como algunos estudios contaron con la participación de estudiantes de todos los grados (Coyle et al, 2009;Destaw et al, 2022;Dubuisson et al, 2011;Hart & Page, 2020;Lalli, 2019), y en otros se tuvo en cuenta la participación de al menos un grupo de estudiantes en un grado específico (Fernández, 2021;González et al, 2021;Illøkken et al, 2021), y un solo estudio centró la investigación en un comedor militar (Carins et al, 2020). En otras investigaciones los estudios se realizaron con diferentes actores como padres de familia, profesores y personal de la cocina del comedor escolar (Burton et al, 2022;Hart & Page, 2020;Lalli, 2019;Mensink et al, 2012;Osorio-Murillo y Amaya-Rey, 2011;Taylor et al, 2020).…”
Section: Técnicas De Recolección E Informaciónunclassified
“…En cuanto a rendimiento académico es poco lo que se conoce sobre la manera en cómo la alimentación y el comedor escolar intervienen en los resultados académicos (Alderman et al, 2010), por tanto, es necesario que investigadores en educación revisen el impacto de las prácticas alimentarias en los resultados académicos, tal como lo recomiendan Taylor et al (2020) y Weaver-Hightower (2011. Sin embargo, algunas investigaciones exploradas sugieren que la alimentación escolar gratuita genera una mejor disposición para aprender, incidiendo en el rendimiento académico (Destaw et al, 2022;Cohen et al, 2021;Illøkken et al, 2021), algunos hallazgos evidencian como la alimentación escolar incide en los resultados exitosos del rendimiento académico en áreas como matemáticas (Ahmed, 2004;Gordanier et al, 2020). Por otra parte, Ayala (2022) señala otro tipo de factores negativos como la efectividad y eficiencia de los programas de alimentación escolar, los cuales no dejan ver las bondades de la alimentación escolar, ni el efecto significativo en los logros de aprendizaje, particularmente de los escolares en Perú.…”
Section: Líneas De Investigaciónunclassified
See 1 more Smart Citation